Emosi Positif Dan Motivasi Hedonis Terhadap Pembelian Impulsif Pada Aplikasi Online Janji Jiwa (Studi Kasus Pada Mahasiswa Universitas Tridinanti Palembang) - Putri, Yuni Adinda (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2023)
Business growth in Indonesia is currently increasing rapidly. Various types of new businesses selling products have sprung up, especially businesses in the food and beverage sector. The current business trend among the public, especially millennials, is the growth of the domestic coffee shop industry, one of which is Kopi Janji Jiwa. This study discusses positive emotions and hedonic motivation toward impulsive purchases in the online application of Soul Promise. The research took a sample of 96 respondents. In analyzing this study using the SPSS application by testing the Validity Test, Reliability Test, Multiple Linear Regression Test, F Test, T-Test, Correlation Coefficient Test, and Coefficient of Determination Test. The results of the study found that positive emotions did not affect impulsive purchases in the online soul promise application.